ANALYSIS OF DETERMINANTS OF FOREIGN POLITICAL AS SOUTH KOREA’S RATIFICATION OF IK-CEPA IN 2021 - Widantya, Putu Gita Dahara Adysrsti; Priadarsini, Ni Wayan Rainy; Sushanti, Sukma (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 4 No 3 (2024): JURNAL DIKSHI, 2025)
The process of forming IK-CEPA goes through a dynamic process, starting from initiation, cancellation, to reactivation and ratification. South Korea's driving factors in ratifying the IK-CEPA are further investigated using the concept of foreign policy and foreign policy determinants by Alex Mintz and Karl DeRouen Jr. This research is qualitative by describing the data descriptively. The data sources used in this study are primary and secondary data sources, with data collection techniques through document study. This research focuses on South Korea's foreign policy, thus the unit of analysis of this research is country-unit analysis. Level of analysis in this research is a combination of individual, state, and international levels of analysis. The formation of the IK-CEPA began during the administration of President Lee Myung-bak, then negotiations were held for seven rounds. However, during the administration of President Park Geun-hye, South Korea decided to stop the IK-CEPA cooperation. After Park Geun-hye was replaced by President Moon Jae-in, South Korea initiated the reactivation of the IK-CEPA until it was officially ratified. Factors driving South Korea to ratify the IK-CEPA are based on determinants of foreign policy which include psychological factors, international factors, and domestic factors. The psychological factors studied are based on psychological factors and Moon Jae-in's leadership type as a determinant of South Korea's foreign policy. Second, international factors are examined based on South Korea's external environment, such as alliances and diplomatic relations. Third, the domestic factors studied are the domestic elements of South Korea, such as domestic economic and political conditions.